1998
DOI: 10.1136/jcp.51.6.479
|View full text |Cite
|
Sign up to set email alerts
|

Adult hypertrophic pyloric stenosis: case report and review.

Abstract: A case of adult hypertrophic pyloric stenosis presented in an older female with no apparent predisposing factors which might be likely to precipitate the condition. There was a history of chronic dyspepsia and occasional episodes of vomiting. No contributory medical history was identified. Barium swallow and follow through showed a markedly reduced emptying time of the stomach. A partial gastrectomy was eventually done and on histopathological examination a diagnosis of adult hypertrophic pyloric stenosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
1
6
0
2
Order By: Relevance
“…Zavala et al [1] reported on a family with both congenital and adult type of hypertrophic pyloric stenosis. This assumption is further supported by the fact that almost 80% of the patients with primary adult hypertrophic pyloric stenosis are men, which is in accordance with the male predominance of congenital pyloric stenosis [1,6,7] .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Zavala et al [1] reported on a family with both congenital and adult type of hypertrophic pyloric stenosis. This assumption is further supported by the fact that almost 80% of the patients with primary adult hypertrophic pyloric stenosis are men, which is in accordance with the male predominance of congenital pyloric stenosis [1,6,7] .…”
Section: Discussionsupporting
confidence: 59%
“…Probably there is no common etiopathogenetic background that could connect these two congenital conditions. However, congenital hypertrophic pyloric stenosis has been described in association with other congenital anomalies, such as congenital mesoblastic nephroma, nephrocalcinosis, recessive polycystic kidney disease, penile agenesis, jejunal atresia, congenital short bowel, congenital diaphragmatic hernia and congenital hypothyroidism [1,7] .…”
Section: Discussionmentioning
confidence: 99%
“…1 In adult patients, causes of pyloric obstruction can be either primary or secondary, with the later most common. 3 Secondary causes include peptic ulcer disease, hiatal hernia, carcinoma, or inflammatory bowel disease. 2 In a series of 100 patients admitted for gastric outlet obstruction, Quigley and colleagues reported that hypertrophic pyloric stenosis was responsible for the obstruction in only 1 patient.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is further supported by the fact that approximately 80% of patients with the adult form of the disease are men, which is in accordance with the male predominance of congenital pyloric stenosis. 3 In addition, this form of primary pyloric stenosis should be differentiated from the secondary form, which is caused by other diseases of the gastrointestinal tract, such as peptic ulcer disease, hypertrophic gastritis, or malignancy. 4 In the adult idiopathic hypertrophic pyloric stenosis (AIHPS), the pylorus is bulbous or fusiform, with its thickest portion at the pyloroduodenal junction 5 (Fig.…”
Section: Adult Idiopathic Hypertrophic Pyloric Stenosismentioning
confidence: 99%